دور مجلس المنافسة في ضبط وتنظيم السوق - ناصــــــر، سهيلة; عبابســـــة، بريـزة; مالــــــكي ،الزهـرة (جامعة الوادي University of El Oued, 2024)
لقد حرست الدولة الجزائرية على تحقيق وممارسة الدولة الضابطة من خلال إنشاء العديد من سلطات الضبط الإدارية المستقلة ، هدفها ضبط النشاط التنافسي في السوق ، ولعل أهم هذه السلطات نجد مجلس المنافسة الذي أنشئ بموجب الأمر 95/06 إلا أنه لم تكن له الفعالية الكافية إلى غاية صدور الأمر 03/03 الذي حدد طبيعته القانونية واعترف له المشرع بالطابع السلطوي والإداري ومنح له صلاحيات واسعة من أجل فرض رقابته على السوق وضبطها وإضفاء طابع الفعالية لدى الجهاز ، ومن أجل أن يقوم بعملها على أحسن وجه ويحسن دورها في السوق عززه المشرع بالقانون 08/12 فأضفى عليه صفة الاستقلالية التي تعد أهم ميزة جاء بها هذا القانون ومن أجل حماية السوق استوجب على الدولة الانسحاب الكلي لأن انسحابها يؤدي إلى فوضى مما يمنع المنافسة النزيهة ، لدا وجب إيجاد ضوابط تشريعية وتنظيمية من أجل فرض توازن بين المصلحة العامة للمجتمع والمصلحة الخاصة للمؤسسات عن طريق بقاء الدولة كضابط للسوق من أجل منع التجاوزات وهذا ما جاء به قانون المنافسة وذلك من خلال دور مجلس المنافسة في حماية السوق وهذا ما تطرقنا له في دراستنا هذه. The Algerian state has ensured the realization and practice of a controlling state through the establishment of many independent administrative control authorities, whose goal is to control competitive activity in the market. Perhaps the most important of these authorities is the Competition Council, which was established pursuant to Order 95/06, but it was not effective enough until the issuance of the law. Order 03/03, which defined its legal nature and the legislator recognized its authoritarian and administrative character and granted it broad powers in order to impose its control over the market, control it, and give the agency a character of effectiveness, and in order for it to carry out its work in the best manner and improve its role in the market, the legislator strengthened it with Law 08/12, adding It has the characteristic of independence, which is the most important feature of this law, and in order to protect the market, it required the state to withdraw completely, because its withdrawal leads to chaos, which prevents fair competition, so it must be createdLegislative and regulatory controls in order to impose a balance between the public interest of society and the private interest of institutions by keeping the state as a market regulator in order to prevent abuses, and this is what the Competition Law came in, through the role of the Competition Council in protecting the market, and this is what we discussed in this study.
ماستر اعمال